Impact of race versus ethnicity on infertility diagnosis between Black American, Haitian, African, and White American women seeking infertility care: a retrospective review - Roxane C. Handal-Orefice, M.D; Melissa McHale, M.D; Alexander M. Friedman, M.D., M.P.H; Joseph A. Politch, Ph.D; Wendy Kuohung, M.D (Elsevier, 2022)
Objective: To determine whether infertility diagnoses differ between Black ethnic subgroups. Design: Retrospective review. Setting: an urban safety-net hospital. Patient(s): Women seeking infertility care between 2005 and 2015. Intervention(s): Charts of women with infertility and polycystic ovary syndrome (International Classification of Diseases, Ninth Revision diagnoses) were reviewed to confirm diagnoses. Data were stratified by race and subsequently by ethnicity to evaluate the differences in infertility diagnoses between Black American, Black Haitian, and Black African women. White American women were used as the comparison group. Main Outcome Measure(s): Infertility diagnoses between Black ethnic subgroups and White women. Result(s): A total of 358 women met the inclusion criteria, including 99 Black American, 110 Black Haitian, 61 Black African, and 88 White American women. Anovulation/polycystic ovary syndrome was the most common diagnosis in each ethnic group, accounting for 40% of infertility among White American, 57% among Black American, 25% among Black Haitian, and 21% among Black African women. There were no significant differences in the individual infertility diagnoses between Black and White women. Between ethnic subgroups, multivariate analysis showed significantly higher odds of infertility because of anovulation/polycystic ovary syndrome in Black American women compared with Black African women (odds ratio [OR], 4.9; 95% confidence interval [CI], 1.4-17.0). Compared with Black African women, higher odds of tubal factor infertility were observed in Black American (OR, 4.7; 95% CI, 1.16-18.7) and Black Haitian women (OR, 4.0; 95% CI, 1.1-14.0). Conclusion(s): Infertility diagnoses were not homogeneous across Black ethnic groups. Studies examining infertility should specify the ethnic subgroups within a race because this may affect results.